Incidence and risk factors for ventilator-associated pneumonia in a developing country: Where is the difference? (2007)
ABSTRACT: Background Latin America exhibits a wide range of differences, compared to developed nations, in genetic background, health services, and clinical research development. It is valid to hypothesize that the incidence and risk factors for ventilator-associated pneumonia (VAP) in our setting may be substantially different of those reported elsewhere. We conducted a study to determine the incidence and risk factors for VAP in a University Hospital from Medellin, Colombia. Methods Prospective cohort study in three intensive care units (ICU) (surgical/trauma, medical, cardiovascular) in a 550-bed University Hospital. Critically ill patients (n=270) who required at least 48 h of mechanical ventilation (MV) between June 2002 and October 2003 were followed until ICU discharge, VAP diagnosis or death. Results Sixty patients (22.2%) developed VAP 5.9±3.6 days after admission. The overall incidence of VAP was 29 cases per 1000 ventilator-days. The daily hazard for developing VAP increased until day 8, and then decreased over the duration of stay in the ICU. The only statistically significant factor after multivariable analysis was gender, with being female reducing 57% the risk of pneumonia (hazard ratios (HR): 0.43; 95% confidence intervals (CI): 0.19–0.96). Conclusions The epidemiologic profile of VAP in terms of incidence, length of stay and clinical course resembles the general pattern described everywhere. Surprisingly, we could not identify any potentially modifiable risk factor for VAP. A comprehensive multicenter study is warranted. It should provide deep insight about the specific microbiological, genetic and clinic features of VAP in our setting.